2012
DOI: 10.5923/j.materials.20110102.11
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Properties of Wheat Straw Reinforced Polyester Composites

Abstract: A study on the flexural properties of wheat straw reinforced polyester composites is presented in this paper.The wheat straw/polyester composites were made as per the hand layup procedure and the instructions provided by the manufacturers. These specimens were then tested in the three point bend configuration in accordance with ASTM D790-07 at a span to depth ratio of 16. Four weight fractions of wheat straw 2%, 4%, 6% and 8% were chosen to be studied. The process-induced voids were studied and it is shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…They observed that flexural modulus decreases with the addition of wheat straw in both results; this reduction is due to the presence of process-induced voids. 9 Obele et al worked on the polypropylene/WSF as well as polypropylene/ WSF/maleic anhydride at different fiber loadings and found that mechanical properties are decreasing as increases of the fiber content but the addition of maleic anhydride improved these properties. 10 Liany et al studied the high-density polyethylene/wheat straw composites incorporated with the various concentrations of magnesium hydroxide, nanoclay, and also used the maleic anhydride-grafted polyethylene as a compatibilizer at constant content.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that flexural modulus decreases with the addition of wheat straw in both results; this reduction is due to the presence of process-induced voids. 9 Obele et al worked on the polypropylene/WSF as well as polypropylene/ WSF/maleic anhydride at different fiber loadings and found that mechanical properties are decreasing as increases of the fiber content but the addition of maleic anhydride improved these properties. 10 Liany et al studied the high-density polyethylene/wheat straw composites incorporated with the various concentrations of magnesium hydroxide, nanoclay, and also used the maleic anhydride-grafted polyethylene as a compatibilizer at constant content.…”
Section: Introductionmentioning
confidence: 99%
“…PCL is more costly than many other synthetic plastics. For different application areas, the use lignocellulosic filler in PCL matrix were investigated (Ruseckaite and Jimenez, 2003;Mishra and Sain, 2009;Dong and Davies, 2011; Lignocellulosic filler has several advantages including abundance, low cost and high modulus of elasticity (Hornsby et al, 1997;Velde and Kiekens, 2002). For this purpose some researchers have used various polymer and lignocellulosic fiber (Donmez Cavdar et al, 2011;Kaymakci et al, 2013;Donmez Cavdar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…When fibre bundle is incorporated into the composite, flexural strength decreases up to 8% loading of fibre bundle. This occurs due to weak interlocking among the matrix molecules and due to the existence of voids inside the composite [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%